Effect of orthodontic treatment needs on oral health related quality of life among the young population in Delhi NCR-region of North India - Tarun Kumar Singh; Preeti Bhagia; Utkarsh Gupta; Deepak Passi; Jyoti Goyal; Garima Yadav; Bhawna Gautam; Swati Jain (Journal of Family Medicine and Primary Care, 2019)
Aim: To assess the effect of orthodontic treatment needs on oral health-related quality of life among the young people of Delhi NCR. Methods: The study was conducted on 12–15 years of individuals attending dental clinic/hospital in Delhi NCR region. Data were collected using Index of Orthodontic Treatment Need -Dental Component and oral health impact profile 14 questionnaire. The Chi-square test was used to analyze the qualitative data. SPSS software version 20 was used for statistical analysis. Results: Orthodontic treatment needs had an almost similar impact on the daily activities of both males and females. The sense of taste was not significantly affected by the need for orthodontic treatment in either males or females. The proportions of orthodontic patients found to have the painful arch, embarrassment, tension, and self-conscious both in males and females. Conclusion: There is a significant correlation of orthodontic treatment needs among oral health-related quality of life.